Electromembrane Extraction of Ofloxacin from Human Plasma and Its Quantification by Capillary Electrophoresis - Mahsa Javan; Behrouz Seyfinejad; Elaheh Rahimpour; Mojtaba Varshochi; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2024)
Background: Application of electromembrane extraction coupled with capillary electrophoresis was studied for ofloxacin extraction from plasma samples. Methods: Ofloxacin migrated from acidic plasma samples through a thin layer of 1-octanol immobilized in the pores of a porous hollow fiber wall into a 10 µL acidic aqueous acceptor solution located inside the lumen of the fiber. Results: Under optimum conditions influencing electromigration (i.e., 20 min of the operation time, stirring speed of 750 rpm, donor phase pH at 4.0, acceptor pH at 3.0, and applied voltage of 30 V across the supported liquid membrane), ofloxacin was extracted from plasma samples with an enrichment factor of 100-fold corresponding to extraction percent of 24%. The calibration curve showed acceptable linearity in the range of 0.2-7.0 µg.mL-1 (R=0.9993). The limits of detection and quantification of 0.05 and 0.2 µg.mL-1 were obtained, respectively. The inter- and intra-day precision and accuracy were obtained below 8.65%. Conclusion: The validated method was successfully processed for the ofloxacin determination in the plasma samples of patients under ofloxacin therapy. There were no interfering peaks which indicates the great selectivity of the developed method.